Does sport-specific experience affect reaction times in the premotor phase? - Onishi, F.; Mineta, S.; Hirose, N. (Journal of Athletic Enhancement, 2019)
Objective: When reacting in a sport-specific situation, athletes use body movements as cues. For example, soccer players use lower body movements as cues, while volleyball players use upper body movements as cues. Despite differences in these focal points, both groups of players use specific cues to recognize sport-specific situations, based on sports-specific experience. This paper aims to investigate how sports-specific knowledge and experience affect reaction times associated with anticipation and prediction by comparing responses during simple and complex tasks performed by athletes with different backgrounds (soccer and volleyball).